2022
DOI: 10.1155/2022/5681206
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Necroptosis-Related lncRNA Signature in Prognosis and Immune Microenvironment for Glioma

Abstract: Background. Glioma is the most common primary brain tumor, representing approximately 80.8% of malignant tumors. Necroptosis triggers and enhances antitumor immunity and is expected to be a new target for tumor immunotherapy. The effectiveness of necroptosis-related lncRNAs as potential therapeutic targets for glioma has not been elucidated. Methods. We acquired RNA-seq data sets from LGG and GBM samples, and the corresponding clinical characteristic information is from TCGA. Normal brain tissue data is from G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Due to their abnormal expression in glioma patients' brain tissue, cerebrospinal fluid, or peripheral circulation, some lncRNAs are thought to be potential biomarkers. Just recently, some necroptosis-related lncRNAs have also been identified which could be used to assess the prognosis and molecular characteristics of glioma (18)(19)(20). However, it is unknown if these lncRNAs are implicated in distinct glioma immune microenvironments or if they may be exploited as novel markers to distinguish cool from hot tumors and as prospective immunotherapy targets for glioma.…”
mentioning
confidence: 99%
“…Due to their abnormal expression in glioma patients' brain tissue, cerebrospinal fluid, or peripheral circulation, some lncRNAs are thought to be potential biomarkers. Just recently, some necroptosis-related lncRNAs have also been identified which could be used to assess the prognosis and molecular characteristics of glioma (18)(19)(20). However, it is unknown if these lncRNAs are implicated in distinct glioma immune microenvironments or if they may be exploited as novel markers to distinguish cool from hot tumors and as prospective immunotherapy targets for glioma.…”
mentioning
confidence: 99%
“…Some scientists have found predictive models for 12 lncRNAs to help assess glioma patients’ prognosis and molecular characteristics. For example, GSEA-GO is associated with Wnt, inositol phosphate metabolism, butyrate metabolism, long-term depression, and taste transduction, improving treatment modality and potentially stimulating future exploration of glioma formation and treatment ( 32 ). Search for specific biomarkers based on markers of necroptosis may be more precise and effective in LGG and GBM management, which may provide new clues for immunotherapy and prognosis.…”
Section: Different Forms Of Rcd Involved In Gliomamentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs), which are > 200 nucleotides in length and have limited protein-coding potential, play an indispensable role in regulating the expression of various cancer-associated genes through various mechanisms, including translation, histone modi cation, post-transcriptional processes, cancer stem cell function, and epithelial-mesenchymal transition [10][11] . Furthermore, numerous studies have reported that lncRNAs are associated with tumor progression and prognosis in patients with LGG [12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%